Digital Operational System Analysis: Sharia Core Banking in Digital Financial Transactions - Sutono Sutono; Sofia Masukah (Indonesian Economic Review, 2025)
The rapid development of digital technology has significantly transformed the banking sector, including Islamic banking, which is required to adapt to digital-based operational systems while maintaining compliance with Sharia principles. One of the key components supporting digital financial transactions in Islamic banks is the digital operational system through Sharia core banking. This study aims to analyze the digital operational system of Sharia core banking in supporting digital financial transactions, focusing on its role, operational mechanisms, and implementation challenges. This research employs a qualitative descriptive approach using a literature study method by reviewing relevant academic journals, books, and official regulations related to digital Islamic banking. The findings indicate that the Sharia core banking system plays a central role as the backbone of digital financial transactions by integrating transaction processing, accounting, reporting, and Sharia compliance control in real time. The system contributes to improving operational efficiency, transaction transparency, service reliability, and internal control while ensuring adherence to Sharia principles through proper contract management. However, the implementation of digital Sharia core banking systems still faces challenges related to technological infrastructure, human resource readiness, and regulatory adaptation. These challenges highlight the need for continuous system development, enhancement of human resource competencies, and regulatory harmonization. This study provides theoretical contributions to the literature on digital Islamic banking and offers practical insights for Islamic financial institutions in optimizing digital core banking systems to support sustainable digital financial services .